Glutamate receptor-interacting protein 1 in D1- and D2-dopamine receptor-expressing medium spiny neurons differentially regulates cocaine acquisition, reinstatement, and associated spine plasticity - Chen, He; Chen, Limei; Yuan, Zhirong; Yuan, Jiajie; Li, Yitong; Xu, Yuesi; Wu, Jieyi; Zhang, Lu; Wang, Guohua; Li, Juan (Frontiers in Cellular Neuroscience, 2022)
Background: Nucleus accumbens (NAc) is involved in the expression of cocaine addictive phenotypes, including acquisition, extinction, and reinstatement. In NAc, D1-medium spiny neurons (MSNs) encode cocaine reward, whereas D2-MSNs encode aversive responses in drug addiction. Glutamate receptor-interacting protein 1 (GRIP1) is known to be associated with cocaine addiction, but the role of GRIP1 in D1-MSNs and D2-MSNs of NAc in cocaine acquisition and reinstatement is still unknown. Methods: Conditioned place preference apparatus was used to establish cocaine acquisition, extinction, and reinstatement in mice models. GRIP1 expression was evaluated using Western blotting. Further, GRIP1-siRNA and GRIP1 overexpression lentivirus were used to interfere with the GRIP1 in NAc. After the behavioral test, brain slices were used to detect spine density by using green fluorescent protein immunostaining. Results: GRIP1 expression decreased in cocaine acquisition and reinstatement. GRIP1-siRNA enhanced cocaine-induced CPP behavior in acquisition and reinstatement, and regulated associated spine plasticity. Importantly, decreased GRIP1 expression that mediated cocaine acquisition and reinstatement was mainly driven by the interference of GRIP1-GluA2 interaction in D1-MSNs, and could be blocked by the interference of GRIP1-GluA2 interaction in D2-MSNs. Interference of GRIP1-GluA2 interaction in D1- and D2-MSNs decreased spine plasticity in D1- and D2-MSNs, respectively. Conclusions: GRIP1 in D1- and D2-MSNs of NAc differentially modulates cocaine acquisition and reinstatement. GRIP1 downregulation in D1-MSNs has a positive effect on cocaine acquisition and reinstatement, while GRIP1 downregulation in D2-MSNs has a negative effect. Additionally, GRIP1 downregulation in D1-MSNs plays a leading role in cocaine acquisition and reinstatement.